Nipple sparing mastectomy: Surgical and oncological outcomes from a national multicentric registry with 913 patients (1006 cases) over a six year period. (February 2016) - Orzalesi, Lorenzo; Casella, Donato; Santi, Caterina; Cecconi, Lorenzo; Murgo, Roberto; Rinaldi, Stefano; Regolo, Lea; Amanti, Claudio; Roncella, Manuela; Serra, Margherita; Meneghini, Graziano; Bortolini, Massimiliano; et al.
Abstract: Background: Nipple sparing mastectomy is deemed surgically and oncologically safe based on a long lasting literature data from reviews of single institution series. This study aims at evaluating surgical and oncological outcomes of NSM on a large multi-institutional scale, by means of the Italian National registry. Methods: In July 2011 a panel of Italian specialists agreed upon and designed a National database of NSM. Centers with at least 150 cancers per year and following the National follow-up schedule guidelines could participate inserting any NSM case performed, retrospectively and prospectively from that moment on. In March 2015 analysis of data was accomplished. Dataset for this study consists of cases performed in the period between January 1st 2009 and December 31st 2014. Results: 913 Women were included in the analysis, for a total of 1006 procedures. Prophylactic mastectomies were 124 (12.3%). MRI utilization increased over time. NSM failure rate, with NAC removal for any reason was 11.5%. NAC necrosis rate was 4.8%. Larger skin-flap necrosis rate was 2.3%. Major surgical complications rate was 4.4%. Oncological outcomes were calculated among primitive EBC cases only: locoregional recurrences rate was 2.9%, NAC recurrence 0.7%. Systemic recurrence rate was 1.0%. Five deaths (0.7%) were registered. Conclusions: More than 10% of NSM procedures are prophylactic mastectomies. MRI is gaining more importance over time. Surgical and oncological results show that NSM is effective. This National multicentric analysis enables a comparison of results with no geographical differences and a "safe" state of the art of NSM in Italy. Highlights: Large NSM series from a national multinstitutional registry. NSM is widespread both for prophylactic and therapeutic mastectomy. Surgical outcomes confirm a low rate of NAC necrosis and complications. Oncological outcomes show safety of NSM with low rate of NAC/skin recurrences.